Analysis of PTNBH Financial Management At Universitas Negeri Semarang - Ariyati Ariyati; Farida Rahmawati; Widya Prananta (Forum Ilmu Sosial)
This research wants to examine the influence of human resource factors, pre-facilities, and budgeting systems that affect the financial management performance of Semarang State University after becoming PTNBH. The method used in this research is quantitative method with multiple regression analysis. The data used in this study are primary data directly obtained from respondents by distributing questionnaires to implementers of work activities within the State University of Semarang. The results concluded that the results of the calculation with the T test on all variables showed the p value <0.05 so that each variable had a significant effect. Thus the quality factor of human resources, pre-facilities, and budgeting systems affect the financial management of universities in Semarang State University, thereby supporting the autonomy of universities in increasing inchome generating.